Is the reciprocating movement per se able to improve the cyclic fatigue resistance of instruments?. (19th August 2013) - Kiefner, P.; Ban, M.; De‐Deus, G.
Abstract Aim To compare cyclic fatigue resistance of two geometrically similar nickel–titanium instruments, used in conditions similar to clinical use in reciprocating and continuous rotary motion. Methodology Four groups of eighteen instruments each, Reciproc® files sizes ISO 25 and 40 (R25 and R40) and Mtwo® files sizes ISO 25 and 40 (M25 and M40), were tested in reciprocating and continuous rotary motion, employing a novel experiment device. An artificial root canal (diameter, 1.4 mm; angle of curvature, 60 °; and curvature radius, 5 mm) was milled into a stainless steel block. To simulate clinical conditions, instead of rotating the file in static position, the set‐up was designed to produce a continuous up‐and‐down pecking motion along the vertical axis of the instrument. Time to fracture (TTF) and push–pull cycles (PPC) were recorded, the number of cycles to fracture (NCF) was determined, and fractured instrument surfaces were examined under a scanning electron microscope (SEM). Results Mean time to fracture was 34.44 ± 8.58 min for R25 in reciprocation motion, 35.77 ± 4.82 min for R40 in reciprocation motion, 12.15 ± 1.74 min for M25 in continuous rotary motion and 13.27 ± 2.02 min for M40 in continuous rotary motion, whereas 28.52 ± 3.27 min for R25 in continuous rotary motion, 23.87 ± 1.52 min for R40 in continuous rotary motion, 31.07 ± 1.79 min for M25 in reciprocation motion and 31.08 ± 3.26 min for M40 in reciprocation motion. There was a significant difference (P < 0.0001) for the cyclic fatigue resistance between the reciprocation motion and the continuous rotary motion groups. Reciproc® files in reciprocating movement had a significantly higher NCF than Mtwo® files, when used in continuous rotation. The highest resistance to failure was shown by Reciproc® files in reciprocation movement, followed by Mtwo® files in reciprocation and Reciproc® files in continuous motion. Mtwo® files in continuous rotary movement had the least resistance. SEM analysis of the fracture surface confirmed typical features of cyclic fatigue failure. Conclusion Reciprocating movement increased the cyclic fatigue resistance of NiTi instruments.